Double - Valentine, Jenny (New York : Hyperion, 2013)
When sixteen-year-old Chap is mistaken for a missing boy, he leaves the home where he has been living temporarily and takes on this new identity, not knowing that it is as dangerous and uncertain as the life he has left behind.
Ages 12 and up.
Keywords: Impersonation -- Fiction; Identity (Philosophical concept) -- Fiction; Missing children -- Fiction; England -- Fiction